Pemikiran Thomas Djamaluddin tentang Salat dan Puasa di Daerah Dekat Kutub - Rizalludin , (University of Muhammadiyah Sumatera Utara, 2018)
With the development of science of hisab today, the time of prayer and fasting can be calculated because the movement of the Sun is relatively fixed. This only applies to areas that have normal day and night turns. However, in extreme areas with latitudes greater than 48° (areas close to the poles), continuous twilight may occur namely continuous twilight and dawn light may even occur at late night so that early dawn and sunset to begin and break the fasting can not be determined. Responding to the issue, some argues that the practice of prayer is worshiped with people who fall asleep while fasting is replaced in other months. Another opinion suggests that to follow the time in the surrounding normal area or follow the areas where the sharia came down, namely Mecca and Medina. Those opinions have imperfect weaknesses in performing Ramadan because it can happen one full month of Ramadan that people can not carry out fasting and the prayer times between different regions vary due to the ever-moving circulation of the Sun. Meanwhile, Thomas Djamaluddin offers a time interpolation solution by taking into account the time before and after the extreme time so that the obligation of five-time prayers can still be held every day and fasting is held in Ramadan. However, this opinion has a weakness that the implementation of isya and subuh prayer and fasting is not appropriate to shari'ah because it is held in the light of twilight is still visible. Keyword: Prayer, Fasting, Areas Near The Poles.